Development of Training Program Using Constructionism Theory to Develop Critical, Creative, Productive, and Responsible Mind (CCPR) of Higher Education Students in Communication Arts in Private Higher Education Institutions - Kanogwon Montiraj, กนกวรรณ มณฑิราช; Arunee Hongsiriwat, อรุณี หงษ์ศิริวัฒน์; พลสารัมย์, พันธ์ศักดิ์ (Dusit Thani College Journal, 2018)
This qualitative and quantitative research dealt with the development of a training program based on constructionism to empower students majoring in Communication Arts in private universities to acquire the following characteristics: critical thinking, creative thinking, productivity and responsibility (CCPR). In doing so, it explored the students’ awareness of these characteristics and the factors that affected the acquisition of CCPR. The main objectives of this study were to design a program based on constructionism to train the students on how to acquire these characteristics. Three hundred and eighty-three questionnaires were collected from students majoring in Communication Arts in private universities and in-depth interviews from administrators and instructors. The data were analyzed and used as guidelines for developing a training program based on constructionism to raise students’ awareness of the importance of CCPR and to teach them how to acquire these characteristics. The findings revealed that the students ranked the importance of CCPR high but the number varied according to the size of university, in that there were more students in a large university ranking it high than those in medium-sized and small universities. The factors that affected the acquisition of CCPR were 1) university administrators, 2) instructors, 3) students, and 4) environment. Consequently, a 32-hour training program was designed based on constructionism. It was divided into 8 units, each of which covered the content related to the four characteristics. The learning involved hands-on workshops in the field of Communication Arts through such tools as computers, mobile phones and Facebook so the students could study using their own tools. At the end of the training, the students’ awareness of CCPR increased. The highest level was that for productivity. The results of this study indicate the students’ awareness level of CCPR, the factors that affected the enhancement of CCPR among these students and the design of a training program that can be used as a part of a course to empower the students to realize such characteristics as critical thinking, creative thinking, productivity and responsibility.